2007
DOI: 10.2466/pr0.101.4.1173-1178
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate Athletic Trainers' Knowledge and Perceptions of Disordered Eating Behaviors in Athletes

Abstract: To assess athletic trainers' perceptions and knowledge regarding disordered eating behaviors and to estimate their confidence in response to a test of knowledge, a cross-sectional mail survey was distributed to a national random sample of 500 athletic trainers from the National Collegiate Athletic Association and National Association of Intercollegiate Athletics. 408 collegiate certified athletic trainers responded (rate of 81.6%). A 30-item questionnaire assessed perceptions of disordered eating behaviors wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Additionally, athletic trainers—i.e., the members of the sports medicine team with the closest contact with the athletes—are not adequately equipped to identify eating disorders without the assistance of these screens. A recent study showed that only 68.1% of certified athletic trainers for colleges had ever attended an education program on disordered eating, and of these, only 28% had done so within the year [25]. A fundamental problem lies in the fact that athletic trainers do not feel as though they receive enough education on working with athletes with eating disorders [26].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, athletic trainers—i.e., the members of the sports medicine team with the closest contact with the athletes—are not adequately equipped to identify eating disorders without the assistance of these screens. A recent study showed that only 68.1% of certified athletic trainers for colleges had ever attended an education program on disordered eating, and of these, only 28% had done so within the year [25]. A fundamental problem lies in the fact that athletic trainers do not feel as though they receive enough education on working with athletes with eating disorders [26].…”
Section: Discussionmentioning
confidence: 99%
“…Turks, et al reported that 44% of their coaches previously attended an eating disorder program compared to coaches in this study (40.9%). Thompson, Yingling, Boardley, and rocks (2007) utilized the same survey in athletic trainers; 67% scored above 80% compared to 14.6% of current participants. lack of knowledge is a concern because administrators set policy and procedure and then monitor its implementation by coaches.…”
Section: Discussionmentioning
confidence: 99%
“…While some evidence indicates that ATs have an adequate level of nutrition knowledge, (Shifflett et al, 2002;Smith-Rockwell, 2001;Torres-McGehee et al, 2012) other data suggest they feel inadequately prepared and equipped to counsel athletes about nutritional issues and identify athletes with disordered eating behaviors for referral. (Bonci et al, 2008;Thompson et al, 2007;Whitson et al, 2006). The interaction between 1) nutrition knowledge and perceived competence of ATs and 2) athletes' perception of their ATs' nutrition knowledge and competence may be an important predictor of whether college athletes choose to utilize these important members of their health care team for nutrition information.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the most frequently cited barrier athletes reported within our focus groups was feeling uncomfortable asking questions about nutrition, which mirrors the discomfort that has been previously reported within samples of ATs in dealing with some nutritional issues. (Bonci et al, 2008;Thompson et al, 2007;Whitson et al, 2006) It is possible that, although inadvertently, the discomfort experienced by an AT with addressing some nutritional issues is perceived by the athletes within their care, resulting in athlete discomfort and a perception that their AT does not have time to talk with them and does not care about their nutritional status. Unfortunately, we were unable to locate any previous reports commenting on whether ATs identify with any of the other barriers the athletes within our sample reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation